Development of Canva-Based Interactive Media to Enhance Basic Teaching Skills in Micro Teaching Courses - Djamila Lasaiba; Tawey G Ratumanan; R Kempa; Lambertus J Lokollo; Mohammad Amin Lasaiba (AL-ISHLAH: Jurnal Pendidikan, 2025)
The integration of interactive digital media is increasingly important in teacher education, particularly in Micro Teaching courses that aim to develop students’ basic teaching skills. However, learning media used in such courses often lack interactivity and visual engagement, limiting students’ participation and skill development. This study employed a Research and Development (RD) approach using the Borg and Gall model to develop Canva-assisted interactive learning media for a Micro Teaching course at FITK IAIN Ambon. The participants were 60 teacher education students, consisting of 20 students in a limited trial and 40 students in a large-scale trial. Data were collected through expert validation sheets, student questionnaires, and pre-test and post-test assessments. The developed media included infographics, instructional videos, and interactive quizzes aligned with Micro Teaching competencies. Expert validation indicated very high content and media validity, with scores for ease of use (85%), clarity (88%), curriculum alignment (90%), and visual design (82%). Reliability testing using the test–retest method produced coefficients ranging from 0.72 to 0.85, indicating high consistency. Descriptive analysis of learning outcomes showed increased post-test scores compared to pre-test scores across all measured indicators. In the limited trial, students’ comprehension, engagement, and motivation increased by approximately 20 points. In the large-scale trial, material comprehension improved from 70 to 92, teaching skills from 65 to 87, and student involvement from 72 to 91. The findings suggest that Canva-based interactive media are associated with improved learning outcomes and teaching skill development in Micro Teaching courses. This study highlights the potential of visually rich and interactive media to support student-centered learning in teacher education, particularly in resource-constrained higher education contexts.